Plasmodium vivax AMA1: Implications of distinct haplotypes for immune response. - Najara Carneiro Bittencourt; Ana Beatriz Iung Enembreck da Silva; Natália Silveira Virgili; Ana Paula Schappo; João Henrique D B Gervásio; Tamirys S Pimenta; Mario A Kujbida Junior; Ana Maria R S Ventura; Rosana M F Libonati; João Luiz Silva-Filho; Hellen Geremias Dos Santos; Stefanie C P Lopes; et al. (PLoS Neglected Tropical Diseases)
In Brazil, Plasmodium vivax infection accounts for around 80% of malaria cases. This infection has a substantial impact on the productivity of the local population as the course of the disease is usually prolonged and the development of acquired immunity in endemic areas takes several years. The recent emergence of drug-resistant strains has intensified research on alternative control methods such as vaccines. There is currently no effective available vaccine against malaria; however, numerous candidates have been studied in the past several years. One of the leading candidates is apical membrane antigen 1 (AMA1). This protein is involved in the invasion of Apicomplexa parasites into host cells, participating in the formation of a moving junction. Understanding how the genetic diversity of an antigen influences the immune response is highly important for vaccine development. In this study, we analyzed the diversity of AMA1 from Brazilian P. vivax isolates and 19 haplotypes of P. vivax were found. Among those sequences, 33 nonsynonymous PvAMA1 amino acid sites were identified, whereas 20 of these sites were determined to be located in predicted B-cell epitopes. Nonsynonymous mutations were evaluated for their influence on the immune recognition of these antigens. Two distinct haplotypes, 5 and 16, were expressed and evaluated for reactivity in individuals from northern Brazil. Both PvAMA1 variants were reactive. Moreover, the IgG antibody response to these two PvAMA1 variants was analyzed in an exposed but noninfected population from a P. vivax endemic area. Interestingly, over 40% of this population had antibodies recognizing both variants. These results have implications for the design of a vaccine based on a polymorphic antigen.